Parents understanding about chronic child disease and future planning (Research, Society and Development, 2021)
Chronic diseases are those that last for more than six months or when there is no propensity to cure. Disabling chronic diseases make the individual unable to perform daily activities, such as walking and talking. When such diseases affect children, there is greater commotion and apprehension in the context of future life planning, generating expectations in parents/caregivers. It is worth emphasizing the importance of good communication between the interdisciplinary team and the family in order to help understand the clinical case and its prognosis. The objective of this research was to reveal the perception of parents about the chronicity of their children's illnesses, the understanding of the information provided by the teams, in addition to planning for the future. This is a descriptive research with a qualitative approach with 11 parents of 09 children who were hospitalized in the pediatric intensive care and inpatient unit of a hospital in the metropolitan region of Porto Alegre, between September and November 2020. Data were collected. through semi-structured open interviews, and the results were presented divided into 04 categories and submitted to the analysis and comparison of the findings. It is concluded that, in general, parents understand the information provided by the health team, and the longer the hospital stay, the better the acceptance of the prognosis. In most cases, parents accept that the disease will not be cured, but expect and plan significant improvements in the condition. In 100% of cases the greatest desire of parents is to be with their children at home.